Analysis of Legal Certainty in Determining the Position, Duties, and Responsibilities of Temporary Notary Officials - Kurniawan, Steven; Dewi, Amelia Sri Kusuma; Wisnuwardhani, Diah Aju (IJBLE Scientific Publications Community Inc., 2023)
The position of a Notary is a crucial part of the Indonesian state that adheres to the principles of a legal state. The Notary is the only public official authorized to create authentic deeds. An authentic deed is a document whose form is determined by the law or is created by or in the presence of a public official authorized for that purpose. This means that an authentic deed has a form stipulated by the law and is created by a public official designated by the law. In the course of performing their duties, notaries may sometimes be unable to fulfill their responsibilities due to reasons such as leave, illness, temporary impediment, or death. Therefore, to continue providing services and being accountable to the public, the position of Temporary Notary Official is established. The procedure for a Temporary Notary Official to perform the duties of a temporarily dismissed notary is explained in Article 80 of the UUJN: